Psd1 Effects on Candida albicans Planktonic Cells and Biofilms - Gonçalves, Sónia; Silva, Patrícia M.; Felício, Mário R.; de Medeiros, Luciano N.; Kurtenbach, Eleonora; Santos, Nuno C. (Frontiers in Cellular and Infection Microbiology, 2017)
Candida albicans is an important human pathogen, causing opportunistic infections. The adhesion of planktonic cells to a substrate is the first step for biofilm development. The antimicrobial peptide (AMP) Psd1 is a defensin isolated from Pisum sativum seeds. We tested the effects of this AMP on C. albicans biofilms and planktonic cells, comparing its activity with amphotericin B and fluconazole. Three C. albicans variants were studied, one of them a mutant deficient in glucosylceramide synthase, conferring resistance to Psd1 antifungal action. Atomic force microscopy (AFM) was used to assess morphological and biomechanical changes on fungal cells. Surface alterations, with membrane disruption and leakage of cellular contents, were observed. Cytometry assays and confocal microscopy imaging showed that Psd1 causes cell death, in a time and concentration-dependent manner. These results demonstrate Psd1 pleiotropic action against a relevant fungal human pathogen, suggesting its use as natural antimycotic agent.